Experiential Learning and Its Impact on Chemistry Education: A Systematic Review of Research Trends - Aulia Rahmah; Endang Widjajanti (Universitas Pendidikan Ganesha, 2025)
Chemistry education continues to face challenges such as low student achievement and the dominance of conventional approaches. This study regularly reviews the implementation of experiential learning in chemistry education. A systematic literature review (SLR) was conducted by searching four databases ScienceDirect, ResearchGate, ACS Publications, and Google Scholar using the keywords “experiential learning chemistry” in English and Indonesian. Twenty articles published between 2012 and 2025 that met the inclusion criteria were analyzed through coding and thematic categorization. The findings show that the use of modules, student worksheets, and games is the dominant strategy (22.2%) in implementing experiential learning. The most frequently examined dependent variables are learning outcomes (25%), conceptual understanding and motivation (12.5%), while the most common topics are basic chemistry (20%), electrochemistry and environmental chemistry (10%). Experiential learning-based media were reported to improve conceptual mastery, engagement, and 21st-century skills. This review contributes by mapping empirical trends and highlighting the novelty that experiential learning benefits not only cognitive achievement but also affective engagement and self-directed learning.